Performance of geosynthetic reinforced/stabilized paved roads built over soft soil under cyclic plate loads. Issue 6 (December 2016) - Abu-Farsakh, Murad; Hanandeh, Shadi; Mohammad, Louay; Chen, Qiming
Abstract: The benefits of using geosynthetics to enhance the performance of pavement constructed over soft subgrade was evaluated using cyclic plate load testing. A total of six test sections, with varying types and layers of geosynthetics and base thicknesses, were constructed inside a 2 m × 2 m × 1.7 m test box. A cyclic load at a frequency of 0.77 Hz was applied through a 305 mm-diameter steel plate. The test sections were instrumented by a variety of sensors to measure the load-associated pavement response and performance. The test results clearly showed the benefits of geosynthetics in significantly reducing the pavement rutting. The test section with double geosynthetics layers performs much better than all other sections studied in this paper. Geosynthetics placed at the base–subgrade interface function more as weak subgrade stabilization than as base layer reinforcement in this study. Finally, the benefits of geosynthetic reinforcement was quantified, within the context of the AASHTOWare Pavement ME Design guide, in terms of increasing the resilient modulus of base course layer and/or reducing the thickness of base aggregate layer in pavement structure. The results of analysis show that for geosynthetics functioning as base reinforcement alone, the value of resilient modulus of the base course layer can be increased by about one quarter and that the thickness of base layer can be reduced by about one third for the pavement sections, with 457 mm thick base and single layer of geosynthetic placed at the base–subgrade interface, tested in this study. For geosynthetics functioning as subgrade stabilization alone, the test results showed that the resilient modulus of subgrade can be almost doubled.